Volunteer motivation: A field study examining why some do more, while others do less. Issue 3 (1st December 2017) - Cady, Steven H.; Brodke, Michelle; Kim, Joo‐Hyung; Shoup, Zachary D.
Abstract: In nonprofit organizations, motivating volunteers for particular activities is challenging because they can take place in unstructured environments. Therefore, members are disengaged despite their initial commitment to the cause. An important opportunity in the literature is to examine motivation from the perspective of the volunteer; and, more specifically, to test for the differential impact that self‐efficacy, collective efficacy, and perceived organizational support have on three motivational outcomes: effort, performance, and satisfaction. Our focus is on volunteer motivation to support a specific event or project. Teasing out the impact of one's efficacious beliefs about their group at the individual level is an important contribution that has yet to be examined. Using data from 285 volunteers, results indicate that collective efficacy and perceived organizational support positively influence volunteer satisfaction. An important contrast we confirmed, unlike self‐efficacy and perceived organizational support, was collective efficacy's negative relationship to effort, which in turn affected performance. We were able to isolate the unique relationships, corroborating extant research with respect to self‐efficacy and perceived organizational support. As a result, the potential for spurious relationships was ruled out, adding credibility to the new findings.